Children and adolescents´ dental treatment in 2001-2013 in the Finnish public dental service - J. Linden; E. Widström; J. Sinkkonen (BMC, 2019)
Abstract Background The Public Dental Service (PDS) in Finland has catered for the overwhelming majority of the young for more than 50 years. They have had examinations, preventive measures and all other necessary treatment free of charge. This study aimed to survey the treatment needs and treatment measures provided for children and adolescents and changes in these during the period 2001-2013. Methods Using each person's unique identifier, data on patients (< 18 years), their oral health (CPI > 2, D + d > 0) and treatment received in the period 2001-2013 were collected retrospectively from municipal databases in five PDS-units covering 320,000 inhabitants. The National Institute for Health and Welfare gave ethical approval. Permission to use local data was received from the Directors in the PDS units. Treatment measures were grouped into 14 categories and patients into three age categories (0-6 years, 7-13 years and 14-17 years). Trend analysis was used to test changes over time. Results About 40,000 children and adolescents visited the PDS each year and 2,488,805 treatment measures were provided for them during the entire study period. The proportion of those in need of treatment decreased from 44.4 to 33.2% during the study period. The most common treatment categories were examinations (613,753, 24.7%), orthodontics (499,033, 20.1%), preventive measures (372,473, 15.0%) and restorative treatment (355,325, 14.3%); these made up 74% of all treatment measures. During the study period, statistically highly significant (p < 0.001***) increasing trends were found for examinations, anaesthesia and the total number of treatment measures, and a significant (p < 0.001***) decreasing trend in restorative treatment were found for all the young. More preventive treatment measures were provided for those not in need of treatment compared with those in need of treatment. Conclusion Although children's oral health had improved and restorative treatment provided had decreased, the total number of treatment measures increased. Healthy children received frequent examinations and high numbers of preventive treatment measures. Targeting treatment according to needs was not satisfactory.